Is a controlled trial of long-term oral anticoagulants in patients with stroke and non-rheumatic atrial fibrillation worthwhile? - Sandercock, P; Warlow, C; Bamford, J; Peto, R; Starkey, I (1986)
A controlled randomised trial large enough to assess the value of anticoagulating stroke patients in atrial fibrillation would be difficult to conduct in the UK and the results would be applicable to only a small proportion of stroke patients. It would be more worthwhile to organise a trial that also assessed the value of other treatments that are simpler and applicable to all stroke patients. A trial that assessed the value of aspirin and beta-blockers against control in all stroke patients would not cost much more than one restricted to comparing anticoagulants against control in patients with stroke and atrial fibrillation but would provide information of more relevance to the management of patients with stroke in the UK.